2019
DOI: 10.15252/embj.2018100986
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation of the DDX 5 helicase RGG / RG motif by PRMT 5 regulates resolution of RNA:DNA hybrids

Abstract: Aberrant transcription‐associated RNA : DNA hybrid (R‐loop) formation often causes catastrophic conflicts during replication, resulting in DNA double‐strand breaks and genomic instability. Preventing such conflicts requires hybrid dissolution by helicases and/or RN ase H. Little is known about how such helicases are regulated. Herein, we identify DDX 5, an RGG / … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 69 publications
4
65
0
Order By: Relevance
“…DDX5, a DEAD-box RNA helicase, has been reported to have a DNA:RNA hybrid unwinding activity (50,51). A recent study using human cell lines found that DDX5 interacts with XRN2 at transcriptional termination regions through its RGG/RG motif to resolve R-loops (51).…”
Section: Jbc Reviews: R-loop Benefits and Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…DDX5, a DEAD-box RNA helicase, has been reported to have a DNA:RNA hybrid unwinding activity (50,51). A recent study using human cell lines found that DDX5 interacts with XRN2 at transcriptional termination regions through its RGG/RG motif to resolve R-loops (51).…”
Section: Jbc Reviews: R-loop Benefits and Risksmentioning
confidence: 99%
“…DDX5, a DEAD-box RNA helicase, has been reported to have a DNA:RNA hybrid unwinding activity (50,51). A recent study using human cell lines found that DDX5 interacts with XRN2 at transcriptional termination regions through its RGG/RG motif to resolve R-loops (51). Although it is not essential for the DDX5 helicase activity in vitro, methylation of the RGG/RG motif of DDX5 by protein arginine methyltransferase 5 (PRMT5) was required for DDX5 to interact with XRN2 and promote R-loop resolution.…”
Section: Jbc Reviews: R-loop Benefits and Risksmentioning
confidence: 99%
“…In addition, when formed, R-loops can be removed by cellular RNA nucleases, including RNase H1 and RNase H2, which specifically cleave the RNA moiety of the R-loops (Wahba et al, 2011) and the 59-39 exoribonuclease 2 (XRN2) which degrades nascent RNA downstream the 39-terminal cleavage site to facilitate transcription termination. XRN2 physically associates with helicase such as Senataxin (Skourti-Stathaki et al, 2011) and DDX5 (Mersaoui et al, 2019). The RNA helicases resolve the DNA/RNA hybrids for subsequent degradation by XRN2 (Skourti-Stathaki et al, 2011;Mersaoui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…XRN2 physically associates with helicase such as Senataxin (Skourti-Stathaki et al, 2011) and DDX5 (Mersaoui et al, 2019). The RNA helicases resolve the DNA/RNA hybrids for subsequent degradation by XRN2 (Skourti-Stathaki et al, 2011;Mersaoui et al, 2019). Deficiency of XRN2 expression causes R-loop accumulation and DNA damage (Morales et al, 2016;Mersaoui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2C; Chen Fig. 2C; Argaud et al 2019;Mersaoui et al 2019). Pre-mRNA splicing and RNA export factors appear to help pull nascent RNAs out from R-loops to facilitate RNA processing and transport, thus preventing R-loop accumulation ( Fig.…”
Section: Promoters As Hotspots For Rbp Actionsmentioning
confidence: 99%